Penyuluhan Kemandirian Pangan dalam Mengatasi Dampak Covid-19 di Desa Timbuolo - Fahrudin Zain Olilingo; Ivan Santoso (Jurnal Pemberdayaan Umat, 2022)
Purpose: This community service aims to provide counseling to the Timbuolo village community to improve understanding and strategies for food independence in overcoming the impact of the Covid 19 pandemic. Method: Extension with the stages of survey, coordination and implementation, the target is focused on farmer groups as the main actors in agricultural production and housewives. Results: The results of the service show that there is an increase in the knowledge, skills and attitudes of rural communities, especially related to the readiness of food production to its distribution, food availability which includes food security, post-harvest processing industry, supply chain efficiency and distribution as well as strategies to deal with it in the future. Conclusions: food security prepared by the community and village government requires innovation in handling and anticipating in the face of a pandemic